Nerves and nerve injuries History, embryology, anatomy, imaging, and diagnostics - Tubbs, R. Shane; Rizk, Elias; Shoja, Mohammadali M. ([Amsterdam]: Elsevier Science and Technology, 2015)
Nerves and Nerve Injuries is the first comprehensive work devoted to the nerves of the body. An indispensable work for anyone studying the nerves or treating patients with nerve injuries, these books will become the 'go to' resource in the field. The nerves are treated in a systematic manner, discussing details such as their anatomy (both macro- and microscopic), physiology, examination (physical and imaging), pathology, and clinical and surgical interventions. The authors contributing their expertise are international experts on the subject. The books cover topics from detailed nerve anatomy.
Includes bibliographical references.
Elsevier
OCLC
Keywords: Nervous system -- Wounds and injuries; Pain; Trauma, Nervous System; Peripheral Nerves; Peripheral Nervous System; Peripheral Nerve Injuries; Nervous system -- Wounds and injuries; Pain; Print books